Activation of 574 new Alzheimer's special care unit beds in the Metropolitan City of Milan. (30th September 2020) - Castelli, B; Centurione, E; Marino, A F; Garau, L; Cofano, R; Ferrara, A; Pannese, C; Raimondi, A; Gandolfi, C E; Da Re, N R
Abstract: Issue: Dementia is among the main causes of disability and dependency in the elderly. It was defined a public health priority by the WHO. The health and social-care system of the Lombardy region (SSR) plays a key role in implementing assistance and care pathways specifically designed for fragile populations, including those affected by dementia and Alzheimer's disease, its most common form. Description of the Problem: The SSR provides residential care options especially conceived for dementia patients, known as Alzheimer's special care units (ASCU). However, waiting lists are concerning, and distribution of these facilities is inconsistent throughout the region. In 2018 there were 981 accredited and SSR-covered ASCU beds in the Metropolitan City of Milan (MCM), translating in 1.26 beds/1000 people aged ≥ 65. With regional legislation (DGR 1046/2018), the SSR proposed activation of new ASCU beds in all territories with less than 2 beds/1000 people aged ≥ 65. The MCM Agency for Health Protection (ATS) thus analyzed the distribution of ASCU beds in afferent districts, defining specific needs for each district. The aim was to fund and activate 574 new ASCU beds homogenously among previously accredited and SSR-covered residential care facilities, reaching the targeted 2 ASCU beds/1000 people aged ≥ 65. Applicant facilities had to respond to specific personnel, technological, therapeutic and structural requirements. Results: Preliminary results indicate 29 residential care facilities applied for evaluation in 2019. The ATS received and evaluated all applications. Following site-inspection, 8 facilities were deemed inappropriate. Lessons: In 2019, 21 residential care facilities were approved for funding and activation of 558 new ASCU beds. Residual beds will be funded in 2020. Main messages: Activation of new ASCU beds in 2019 and 2020 increased specialized long-term care beds for dementia patients by almost 60%, allowing a more homogenous distribution among MCM districts. Key messages: The health and social-care system of the Lombardy region proposed activation of new Alzheimer's special care units beds in all territories with less than 2 beds/1000 people aged ≥ 65. Activation of 574 new Alzheimer's special care units beds increased by almost 60%, allowing a more homogenous distribution among Metropolitan City of Milan districts.